(untitled) (Acta Scientiarum. Agronomy, 2017)
The aim of this study was to identify the best conditions for drying and storing soybeans and sunflower grains to maintain their quality. In the first experiment, the soybeans were found to have initial moisture contents of 25 and 19% (w.b.) at different drying air temperatures (75, 90, 105, and 120°C). In the second step, the soybeans were evaluated after they were stored in paper bags and plastic polyethylene at temperatures of 3, 10 and 23°C for six months. In the third experiment, sunflower grains were tested after exposure to drying air temperatures of 45, 55, 65, and 75°C, and under storage conditions of 25°C and 50%, 20°C and 60%, 30°C and 40% RH over six months in paper bags and raffia. Drying the sunflower seeds at 45°C and storing them at 30°C and 40% RH led to higher oil yields and lower acid numbers. The oil that was extracted from the acid number was higher for soybean grains that were dried down from initial concentrations of 25% water at a drying air temperature of 120°C. The air temperature in storage at 3°C favored for yield and reduction of the soybean oil acidity.